2013
DOI: 10.1002/jcu.22044
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‐enhanced sonography for screening of vascular complication in recipients following living donor liver transplantation

Abstract: The purpose of this article is to discuss the role of CEUS for screening of vascular complication in recipients admitted to ICU following LDLT, effect of microbubble contrast agent on Doppler phenomenon, CEUS technique, and illustrate CEUS findings in recipients with complication following LDLT. CEUS can enhance the role of US in the diagnosis of postoperative vascular complication in recipients following living donor liver transplantation at the bedside.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…It allows to show small thrombus in a peripheral portal branch [108,110] . In a retrospective evaluation of 23 pati ents, CEUS was used as an additional diagnostic method to DUS, CT and magnetic resonance imaging [110] .…”
Section: Summary Of the Clinical Characteristics About Harmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows to show small thrombus in a peripheral portal branch [108,110] . In a retrospective evaluation of 23 pati ents, CEUS was used as an additional diagnostic method to DUS, CT and magnetic resonance imaging [110] .…”
Section: Summary Of the Clinical Characteristics About Harmentioning
confidence: 99%
“…DUS protocols vary widely worldwide among liver transplant centers, but most teams recommend performing DUS daily (some authors recommend twice daily) in the immediate postoperative period until POD 5 or in the presence of abnormalities of liver function tests or a clinical suspicion of the diagnosis [106109] . Recently, other authors have proposed the use of CEUS to avoid frequent false-positive results after DUS [108,110] . CEUS may help in assessing the severity of portal insufficiency, Table 6 Portal vein thombosis highlights…”
Section: Summary Of the Clinical Characteristics About Harmentioning
confidence: 99%
“…In this study, we used CEUS as a postoperative routine imaging examination method. CEUS, has been widely used for the differential diagnosis of abdominal organs with space-occupying lesion ( 15 , 16 ), and it has also been applied for the diagnosis of vascular complications following liver transplantation ( 17 19 ). Ultrasound contrast agent, which also served as a blood pool tracer, can be used in real-time ultrasound contrast imaging to identify large blood vessels and the micro-vascular system ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that ultrasound contrast agents have a low incidence of allergic reactions which only occurs in one out of ten thousand cases, according to previous studies (18,19). Prior studies have revealed a relatively high accuracy (> 90%) of CEUS for the diagnosis of postoperative vascular complications including HAT, HAS, PVT and PVS (10,20,21). However, these individual studies only involved a limited number of patients and therefore, the actual diagnostic value of CEUS could not be determined.…”
Section: Introductionmentioning
confidence: 99%